Pelaksanaan Kegiatan Ekstrakurikuler Tahfidz di MTs YPI Subulul Huda Saentis - Neliwati; Aliyah Putri; Ayu Lestari; Elda Arzetin Elsil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Adolescence is a time of searching for identity. Therefore, children need to be directed towards positive things. One of them is memorizing the Al-Qurna so that children have morals that are in accordance with the Al-Quran, considering that nowadays many teenagers' morals deviate from the values ​​contained in the Al-Quran. The tahfidzul quran extracurricular program is a superior program offered by MTs Yayan Islamic Education Subulul Huda Saentis. Tahfidzul Koran is implemented so that children read the Koran more often and love the Koran more and practice it in their daily lives. This research aims to describe the implementation of extracurricular tahfidzul quran, the methods applied, and the implementation system of the tahfidzul quran program at MTs Islamic Education Foundation Subulul Huda Saentis. This type of research is qualitative research (Field Research), namely empirical study by going directly to the research location on the phenomena that occur. This research is descriptive qualitative in nature. Qualitative research aims to understand events experienced by research subjects, such as behavior, by means of descriptions in the form of words and language. To collect data in this research, the author used interview and documentation methods. In analyzing the data obtained from the research results, the author uses data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results of the research show that the process of implementing the tahfidzul quran extracurricular program at MTs Islamic Education Foundation Subulul Huda Saentis consists of three activities: planning, implementation and evaluation. The activities implemented are in the form of rote deposits, sima'an and muraja'ah. In general, students memorize mixed methods. The factors that influence the process of tahfidzul quran activities are grouped into two, namely supporting factors and inhibiting factors.